Quantum dot photoluminescence as charge probe for plasma exposed surfaces. (22nd December 2022) - Hasani, M; Klaassen, G; Marvi, Z; Pustylnik, M; Beckers, J
Abstract: Quantum dots (QDs) are used as nanometer-sized in situ charge probes for surfaces exposed to plasma. Excess charges residing on an electrically floating surface immersed in a low-pressure argon plasma are detected and investigated by analysis of variations in the photoluminescence spectrum of laser-excited QDs that were deposited on that surface. The experimentally demonstrated redshift of the PL spectrum peak is linked to electric fields associated with charges near the QDs' surfaces, a phenomenon entitled the quantum-confined Stark effect. Variations in the surface charge as a function of plasma input power result in different values of the redshift of the peak position of the PL spectrum. The values of redshift are detected as 0.022 nm and 0.073 for 10 and 90 W plasma input powers, respectively; therefore indicating an increasing trend. From that, a higher microscopic electric field, 9.29 × 10 6 V m −1 for 90 W compared to 3.29 × 10 6 V m −1 for 10 W input power, which is coupled to an increased electric field in the plasma sheath, is sensed by the QDs when plasma input power is increased.